Age-related changes of dental pulp tissue after experimental tooth movement in rats - Martina Von Böhl; Yijin Ren; Anne M. Kuijpers-Jagtman; Piotr S. Fudalej; Jaap C. Maltha (PeerJ, 2016)
It is generally accepted that the effect of orthodontic tooth movement on the dental pulp in adolescents is reversible and that it has no long-lasting effect on pulpal physiology. However, it is not clear yet if the same conclusion is also valid for adult subjects. Thus, in two groups of rats, aged 6 and 40 weeks respectively, 3 molars at one side of the maxilla were moved together in a mesial direction with a standardized orthodontic appliance delivering a force of 10 cN. The contralateral side served as a control. Parasagittal histological sections were prepared after tooth movement for 1, 2, 4, 8, and 12 weeks. The pulp tissue was characterized for the different groups, with special emphasis on cell density, inflammatory cells, vascularity, and odontoblasts. Dimensions of dentin and the pulpal horns was determined and related with the duration of orthodontic force application and age ware evaluated. We found that neither in young nor in adult rats, force application led to long-lasting or irreversible changes in pulpal tissues. Dimensional variables showed significant age-related changes. In conclusion, orthodontic tooth movement per se has no long-lasting or irreversible effect on pulpal tissues, neither in the young nor in the adult animals.